Gunning for Gun Control: A State by State Analysis of the Effects of Gun Control Policies on Firearm Mortality Rates - Robinson, Jade L (2016)
Gun control is not a new concept; however, due to the growing amount of supporting non profits and recent mass shootings, gun control is becoming a common topic both amongst researchers and the general public. Currently, gun control is a state issue and thus should be studied on a state by state basis. This study examines state gun control policies and firearm mortality rates to determine if there is a correlation between gun control policies and the firearm mortality rate. The years covered by this study were 2000-2014 and nine states were sampled. Two out of the nine states were found to have a statistically significant negative correlation between the gun control and the firearm mortality rate. Confounding variables were also studied for each state that was found to support the hypothesis such as demographics and the economics of each state. Further research still needs to be done to determine the cause and effects of firearm violence as well as possible prevention strategies